Ciliary muscle contraction force and trapezius muscle activity during manual tracking of a moving visual target. - Domkin, Dmitry; Forsman, Mikael; Richter, Hans O. (Journal of Electromyography & Kinesiology, 2016)
Previous studies have shown an association of visual demands during near work and increased activity of the trapezius muscle. Those studies were conducted under stationary postural conditions with fixed gaze and artificial visual load. The present study investigated the relationship between ciliary muscle contraction force and trapezius muscle activity across individuals during performance of a natural dynamic motor task under free gaze conditions. Participants (N=11) tracked a moving visual target with a digital pen on a computer screen. Tracking performance, eye refraction and trapezius muscle activity were continuously measured. Ciliary muscle contraction force was computed from eye accommodative response. There was a significant Pearson correlation between ciliary muscle contraction force and trapezius muscle activity on the tracking side (0.78, p<0.01) and passive side (0.64, p<0.05). The study supports the hypothesis that high visual demands, leading to an increased ciliary muscle contraction during continuous eye-hand coordination, may increase trapezius muscle tension and thus contribute to the development of musculoskeletal complaints in the neck-shoulder area. Further experimental studies are required to clarify whether the relationship is valid within each individual or may represent a general personal trait, when individuals with higher eye accommodative response tend to have higher trapezius muscle activity.